Neuro-Pedagogical Framework for Attention Development in Early Childhood: Integrating Attention Network Theory, Neuroplasticity, and Islamic Education - MURTAFIQOH HASANAH; Kesuna Hilyati Fadhila; Rizkiah Putri Yaman; Ulfa Malini (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2026)
Attention is a fundamental neurocognitive function that underlies learning, executive functioning, and the internalization of moral values during early childhood. Despite growing evidence from educational neuroscience regarding the roles of attention networks and neuroplasticity in learning, the translation of these findings into pedagogical practices remains limited, particularly within the context of Islamic education. This study aims to develop a conceptual neuro-pedagogical framework by integrating Attention Network Theory, neuroplasticity, and Islamic educational principles as a theoretical foundation for attention development in early childhood. Employing a literature review design, relevant publications from educational neuroscience, developmental psychology, cognitive neuroscience, and Islamic education were systematically synthesized using thematic analysis. The synthesis focused on three interconnected themes: (1) the neurobiological mechanisms of the alerting, orienting, and executive control networks; (2) neuroplasticity and learning experiences during sensitive developmental periods; and (3) Islamic pedagogical principles, including ta'dīb (habituation), uswah hasanah (role modeling), qiṣaṣ (storytelling), and tafakkur (reflective practice). The analysis indicates that attention functions as a neurocognitive gateway through which meaningful, emotionally engaging, and repeated learning experiences induce experience-dependent neuroplasticity, strengthening neural circuits associated with executive function, self-regulation, and moral reasoning. Furthermore, Islamic pedagogical practices align closely with contemporary neuroscientific evidence by providing multisensory, socially interactive, and emotionally meaningful learning experiences that optimize attention and facilitate long-term value internalization. This article proposes a novel neuro-pedagogical framework positioning attention as the central mechanism linking brain plasticity with Islamic character education. The framework offers an interdisciplinary theoretical foundation for designing brain-based pedagogical strategies that promote school readiness, executive functioning, and holistic character development in early childhood. Keywords: educational neuroscience; attention network theory; neuroplasticity; Islamic education; early childhood; brain-based pedagogy